Sectoral slowdowns in the UK: Evidence from transmission probabilities and economic linkages - Eva Janssens; Robin Lumsdaine (Tinbergen Institute, 2021)
This paper studies shock transmission across macroeconomic sectors in the UK, using data from the Bank of England's Flow of Funds statistics. We combine two different approaches to quantify the spread of shocks to assess whether sectors with large bilateral economic linkages as measured through network data have a greater statistical likelihood of shock transmission between them. The combination of both approaches reveals the Monetary Financial Institutions sector's role as shock absorber, and identifies the most important channels of shock transmission. The inferential discrepancies between network data and the actual spillovers highlight the contribution of the proposed methodology.
Keywords: E37; E32; E01; G01; 330; Flow of Funds; contagion; epidemiology; intersectoral networks; Gibbs sampling; Bayesian priors